Applications of Machine Vision in Agriculture - Paita, Bernabe L. (Philippine Engineering Journal; Vol 19 No 1 (1998), 2021)
Machine vision is an emerging field of technology that is expected to create a pervasive impact in the future. A simple definition of machine is “the ability of a machine to see”. As a sensory input, machine vision can be made a feedback to closed-loop control system such as robotic applications. Sorting for quality and feature recognition are some of the most common applications of machine vision. In this paper, the development of machine vision systems was reviewed and highlighted. Several machine vision configurations are proposed that can be subjects of future research work.